Criminal statistics: Implementation of diversion against criminal acts for children in violation of the law (BIS Humanities and Social Science, 2026)
The numerous criminal cases involving children who have to face the law constitute a current and factual problem, a social and criminal phenomenon that has raised concerns among parents in particular, the public in general, and law enforcement. Children have the right to special protection, particularly within a judicial system that prioritizes the concept of justice for children in conflict with the law. One way to protect children from the judicial and criminal process is through diversion. Diversion refers to an intervention that provide juvenile offenders with an opportunity to not be formally processed and charged. This study aimed to determine the implementation of diversion for juvenile offenders according to criminology statistic as well as the efforts to implement diversion for juvenile offenders. This study was empirical normative research conducted using a statutory approach, a structural approach, and an interdisciplinary approach. The data sources in this study consisted of primary data sources and secondary data sources and were collected using library research and interview. The results of this study indicate that, given the obligation of investigators to conduct diversion in juvenile cases, investigators at the Yogyakarta Police have made every effort to implement diversion in juvenile cases. Regarding the obstacles encountered in implementing diversion, these are both internal and external. To date, the Yogyakarta Police have not taken any action if the implementation of diversion for crimes committed by juveniles fails.